The Chinese Constitution of Central Asia Regions and Intertwined Actors in International Relations - Godehardt, N.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
China's commitments in Central Asia illustrate how regional foreign policy works and how long-standing principles of Chinese foreign policy might be revised in the near future. China's rise has 'moved' Asia, which is why it seems that what we have traditionally regarded as the geographic and political scope of Asia might actually considerably change in the near future. Nadine Godehardt gives crucial insights into the Chinese expert discourse on Central Asia - analyzing how Chinese experts define Central Asia when they talk and write about policy issues related to China's immediate Western neighbourhood. In this context, she gives an inside perspective on Chinese voices whose meanings are rarely examined in Chinese International Relations studies.
Keywords: Ethnology—Asia.; Asia—Politics and government; Economic development; International relations; Diplomacy; Asian Culture; Asian Politics; Development Theory; International Relations; Development Studies; Diplomacy